1996
DOI: 10.2307/1243859
|View full text |Cite
|
Sign up to set email alerts
|

Information Asymmetry as a Reason for Food Industry Vertical Integration

Abstract: Three trends that have been subject to recent discussion are a movement away from undifferentiated agricultural commodities toward more specialized products, reduced reliance on open markets for raw agricultural products, and a movement toward agricultural industrialization. Recent research suggests that demographic trends may be causing the first trend, while the other two are closely related phenomena. This research suggests that information externalities, arising from uncertainty concerning the nature of fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
67
0
4

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(75 citation statements)
references
References 0 publications
4
67
0
4
Order By: Relevance
“…Quite clearly the spot market would be unable to coordinate and synchronise the real time supply of 1.27 million and 3.6 million tons, respectively, of a highly perishable product like sugarcane. The study, therefore, agrees with a large body of literature that has concluded that the spot market cannot be synchronised with respect to ensuring the continuous supply of a uniform quality raw commodity (Glover, 1984(Glover, , 1994Kilmer, 1986;Mahoney, 1992;Hennessy, 1996;Azzam, 1996). The use of specification contracting, in the absence of interlocking factors, is also not recommended as a way to co-ordinate the transaction characteristics of the sugar supply operations.…”
Section: Strategic Alliancesupporting
confidence: 78%
“…Quite clearly the spot market would be unable to coordinate and synchronise the real time supply of 1.27 million and 3.6 million tons, respectively, of a highly perishable product like sugarcane. The study, therefore, agrees with a large body of literature that has concluded that the spot market cannot be synchronised with respect to ensuring the continuous supply of a uniform quality raw commodity (Glover, 1984(Glover, , 1994Kilmer, 1986;Mahoney, 1992;Hennessy, 1996;Azzam, 1996). The use of specification contracting, in the absence of interlocking factors, is also not recommended as a way to co-ordinate the transaction characteristics of the sugar supply operations.…”
Section: Strategic Alliancesupporting
confidence: 78%
“…It therefore comes as no surprise that smallholder participation in green beans and passion fruit went down and the spot market disappeared as a market institution during the 1990s, while a number of very large farms have been set up as part of vertically integrated structures. This development reflects trends in developed countries, where increased vertical integration is often a response to the demand for more complex products due to food safety requirements or other quality aspects (Hennessy 1996). The success in using smallholders in the 1970s and 1980s depended critically on the possibility of segmenting the supply chain into a production sector and a trading sector.…”
Section: Eu Food Safety Reformmentioning
confidence: 97%
“…This can be done in several ways. Vertical integration is one such way (Barzel 1985, Hennessy 1996. Such integration might be achieved by creating a large producer-exporter company.…”
Section: Vertical Integrationmentioning
confidence: 99%
“…Each firm in the data was carefully analyzed using its annual 10-K report to determine whether it was an integration strategy (Pepsico) or a diversification strategy (Sara Lee). Hennessy (1996) summarizes the integration literature in agricultural economics. He suggests that firm structure, desire to reduce variability in supply, and cost of testing for quality are the three most common reasons cited for integration in the food economy.…”
Section: Literature Reviewmentioning
confidence: 99%